Ferritinophagy, a form of autophagic ferroptosis: New insights into cancer treatment - Sun, Kai; Li, Chenyuan; Liao, Shichong; Yao, Xinrui; Ouyang, Yang; Liu, Yi; Wang, Zhong; Li, Zhiyu; Yao, Feng (Frontiers in Pharmacology, 2022)
Ferritinophagy, a form of autophagy, is also an important part of ferroptosis, a type of regulated cell death resulting from abnormal iron metabolism involving the production of reactive oxygen species. As ferroptosis, autophagy and cancer have been revealed, ferritinophagy has attracted increasing attention in cancer development. In this review, we discuss the latest research progress on ferroptosis, autophagy-associated ferroptosis led by ferritinophagy, the regulators of ferritinophagy and promising cancer treatments that target ferritinophagy. Ferritinophagy is at the intersection of ferroptosis and autophagy and plays a significant role in cancer development. The discussed studies provide new insights into the mechanisms of ferritinophagy and promising related treatments for cancer.